2002
DOI: 10.1038/sj.cdd.4401068
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death eliminates all but one embryo in a polyembryonic plant seed

Abstract: Development of multiple embryos from a single zygote, the phenomenon called monozygotic polyembryony, is a widespread reproductive strategy found in higher plants and especially in gymnosperms. The enigma of plant monozygotic polyembryony is that only one embryo in a polyembryonic seed usually survives while the others are eliminated at an early stage. Here we report that programmed cell death (PCD) is the major mechanism responsible for elimination of subordinate embryos in a polyembryonic seed. Using postfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 22 publications
2
67
2
Order By: Relevance
“…21 We found that somatic embryo development of Norway spruce is similar to zygotic embryogeny of Pinaceae, even though embryo origin is different in each case (i.e., somatic cells in proembryogenic mass versus zygote). 21,22 Our more recent studies suggest that autophagic programmed cell death regulates active shape remodeling during both somatic and zygotic embryo development, 23,24 and that dysregulation of this cell death leads to embryonic aberrations. 25 Using somatic embryos of Norway spruce, we characterized the cell biological pathway of autophagic death in the suspensor, a temporal structure, which is composed of the cells at successive steps of the death pathway and is finally eliminated during late embryogeny.…”
Section: Introductionmentioning
confidence: 99%
“…21 We found that somatic embryo development of Norway spruce is similar to zygotic embryogeny of Pinaceae, even though embryo origin is different in each case (i.e., somatic cells in proembryogenic mass versus zygote). 21,22 Our more recent studies suggest that autophagic programmed cell death regulates active shape remodeling during both somatic and zygotic embryo development, 23,24 and that dysregulation of this cell death leads to embryonic aberrations. 25 Using somatic embryos of Norway spruce, we characterized the cell biological pathway of autophagic death in the suspensor, a temporal structure, which is composed of the cells at successive steps of the death pathway and is finally eliminated during late embryogeny.…”
Section: Introductionmentioning
confidence: 99%
“…The latter polyamines are needed for the differentiation of the embryonic axial tier of early embryos (unpublished data). Filonova et al (2002) have proposed that pro grammed cell death (PCD) is the major mechanism responsible for the competitive elimination of sub ordinate embryos in polyembryonic seeds. PCD is claimed to halt 'competition' among monozygotic embryos and ensure the survival of one embryo by a yet undefined 'autocatalytic self destruction pro gram'.…”
Section: Diagnostic Specificity and Genotype Cryopreservationmentioning
confidence: 99%
“…A study by Filonova et al 6 revealed that the multiple subordinate embryos differentiated from a single zygote in Scots pine (Pinus sylvestris) undergo highly ordered selfdestruction, while a single dominant embryo survives and develops to maturity. The morphotype of this form of PCD does not adhere to most of the apoptosis-like hallmarks (except for DNA fragmentation), but rather features classic signs of autophagic cell death.…”
mentioning
confidence: 99%
“…Although the primary signal triggering this PCD is as yet unknown, the authors provide indirect evidence for the maternal control of the demice of subordinate embryos in a pine seed, implicating a PCDtriggering role for the female gametophyte. 6 The latter is a haploid embryo-nourishing tissue being substituted for triploid endosperm in flowering plants during evolution. 8 Plants represent one of the oldest phyla of eukaryotes.…”
mentioning
confidence: 99%
See 1 more Smart Citation